Magyarország konvergencia programja és a világgazdasági válság - Gősi, János (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The convergence program of Hungary and the world economic crisis. The international financial and real economy crisis reached Hungary in the autumn of 2008, too. The crisis made the completion of the 2009. yearly state budget difficult very much and the continuation of the convergence program according to its plan, because the balance of the state budget is decaying because of the economical recession.